Isolated “on-pump” tricuspid valve repair through right-sided anterolateral thoracotomy by modified femoral-monocaval cannulation in patients with repeated heart intervention – a safe and effective surgical alternative - V. V. Osaulenko; V. O. Hubka; K. O. Chmul; R. I. Budahov (Сучасні медичні технології)
Tricuspid valve dysfunction has always been considered less clinically important than left heart valve disease. Disruption of the tricuspid valve can lead to cardiac dysfunction, causing severe and irreversible complications in patients if not treated in time. Reoperations for tricuspid valve insufficiency are surgical procedures associated with particularly high peri- and postoperative risk. The optimal timing and strategies for surgical intervention in isolated tricuspid valve insufficiency remain controversial.